Earnings Management Detection Using Digital Analysis: A Concept in Benford’s Law - Chandra Das, Ramesh (Research Developments in Arts and Social Studies Vol. 1, 2022)
This study examines earnings management of the companies using Benford’s law. This is a probability technique and used as a hand tool by the investigator. Using large sample of Indian public listed companies (34,346 firm-year observations) from 2000 to 2014, the study examines the income statement and balance sheet data whether the numbers in data follow Benford’s law distribution. Further data is segregated based on ownership concentration such as business group firms vs. standalone firms and based on firm specific parameter such as large size vs. small size firms to analysis whether the numbers in data follow Benford’s law distribution. The study uses “first digit”, “second digit” and “first two digits” analysis for examining the conformity of Benford’s law. The financial statement variables such as total assets, receivables, fixed assets, property, plant and equipment, inventory, current assets, current liabilities, sales, selling and distribution expenses, cost of goods sold, cash, earnings before interest and taxes (EBIT), direct tax, indirect tax are considered for analysis of the study. The result finds that data have anomalies under Benford’s law distribution. Further analyses indicate that business group firms indulge more data anomalies than standalone firms. Small size firms have more data anomalies than large size firms in Indian context. The anomalies of data instigate for further investigation of data.